Independent work of students as a necessary element of education at the university - Volkova, Yu. V.; Волкова, Юлія Володимирівна (My University, 2021)
In recent decades, the amount of knowledge that a student must acquire during the period of study at a medical university has increased dramatically. In this regard, the training of highly qualified specialists, competitive in the labor market, as well as capable of competent, responsible and effective activities in their specialty is impossible without increasing the role of students' independent work aimed at stimulating their professional growth and fostering their creative activity [1].